The reality of management by roaming practice of principles of Tatweer schools in Riyadh - Al-Hawishl, Nof Ahmed (Journal of Educational and Psychological Sciences, 2019)
The aim of this research is to recognize the reality of management by roaming practice of principles of Tatweer schools in Riyadh, through answering the main question of the research:What is the reality of management by roaming practice of principles of Tatweer schools in Riyadh?And for achieving that the researcher used the descriptive approach and the survey method, the questionnaire was used as a tool of the research consisting of (47) clauses and distributed over three axes. The sincerity and stability of the tool was confirmed by appropriate statistical and educational methods. The research has found out many results the most notably is that management by roaming practice of principles of Tatweer schools in Riyadh in all its fields was in a very high degree with a general average reached (4.46) of the very high response category, where the guidance field ranked first with an arithmetic average of (4.67) of the very high response category, followed by organization field with an arithmetic average of (4.49) in the very high response category, then the field of ​​planning with an arithmetic average of (4.39) in the very high response category, while the supervision field was in the last order with an arithmetic average of (4.26) in the very high response category.And the center of the obstacles of management by roaming practice of principles of Tatweer schools in Riyadh was in a high level with an arithmetic average of (3.81) in the high response category. The study also mentioned that there were no statistically significant differences at the level of significance of (0.05) in the view of the sample attributable to variable years of experience, variable qualification and variable size of the building, while the focus of the proposals that contribute to management by roaming of the directors of the Tatweer schools in Riyadh, has a high degree of approval with an arithmetic average of (4.01) in the high response category.
Keywords: development; management by wandering; directing; planning; practice